2022
DOI: 10.3389/fcvm.2022.993142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of energy metabolism-related biomarkers for risk prediction of heart failure patients using random forest algorithm

Abstract: ObjectiveEnergy metabolism plays a crucial role in the improvement of heart dysfunction as well as the development of heart failure (HF). The current study is designed to identify energy metabolism-related diagnostic biomarkers for predicting the risk of HF due to myocardial infarction.MethodsTranscriptome sequencing data of HF patients and non-heart failure (NF) people (GSE66360 and GSE59867) were obtained from gene expression omnibus (GEO) database. Energy metabolism-related differentially expressed genes (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Among them, MAPK1 is a biomarker of heart failure, which is closely related to the occurrence and development of heart failure; [31] MAPK14 is involved in the process of energy metabolism related to heart failure. [32] TP53 is an important tumor suppressor gene in the human body. Transcriptomics studies have found that mice with TP53 gene deletion can partially save myocardial fibrosis, myocardial cell apoptosis, non-muscle cell proliferation, left ventricular dilatation and dysfunction, and can slightly improve the survival rate of dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, MAPK1 is a biomarker of heart failure, which is closely related to the occurrence and development of heart failure; [31] MAPK14 is involved in the process of energy metabolism related to heart failure. [32] TP53 is an important tumor suppressor gene in the human body. Transcriptomics studies have found that mice with TP53 gene deletion can partially save myocardial fibrosis, myocardial cell apoptosis, non-muscle cell proliferation, left ventricular dilatation and dysfunction, and can slightly improve the survival rate of dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A key advantage of RF is its ability to reduce overfitting by extracting a subset of data via sampling, then generating decision trees that are independent of each other and based on small numbers of variables. 16 This approach reduces the cost function; it improves prediction results by majority voting and evaluating the importance of independent variables. In an RF model, each decision tree represents a class prediction; the class choice made by the greatest proportion of trees reflects the model’s prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Information entropy and weight (%) analysis of the above evaluation parameters based on the EWM was performed, and the performance of each target was ranked according to the distance from positive ideal solution, distance from negative ideal solution and the composite score index by the TOPSIS algorithm ( 37 ). SVM and RF machine learning algorithms were constructed using the DALEX R package for bidirectional targets, and the diagnostic performance of both models was evaluated by receiver operating characteristic (ROC) curves and associated area under the curve (AUC) ( 38 ).…”
Section: Methodsmentioning
confidence: 99%